2020
DOI: 10.1155/2020/8863645
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Damage Characteristics and Energy Dissipation of Rocks with a Vertical Hole under Cyclic Impact Loads

Abstract: This study systematically investigates the failure patterns, energy dissipation, and fracture behavior of rock specimens containing a vertical hole under impact loads. First, an improved damage calculation equation suitable for the analysis of rock specimens with a vertical hole is obtained based on the one-dimensional stress wave theory and the interface continuity condition. After that, the Hopkinson pressure bar (SHPB) device was used to conduct cyclic impact tests with different impact pressures and impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…It should be noted that the dissipated energy ratio is larger than the elastic energy ratio after peak strength because of the crack growth. Previous studies have shown that during the process from the elastic stage, plastic stage to the failure stage in the stress-strain curve, there is always energy exchange with the outside world, and energy is constantly released to the outside world to maintain dynamic balance [39]. Through the experimental results of sandstone with different water content under cyclic loading, the water can weaken the sandstone underneath the Bohai Sea.…”
Section: Energy Evolution Characteristicsmentioning
confidence: 95%
“…It should be noted that the dissipated energy ratio is larger than the elastic energy ratio after peak strength because of the crack growth. Previous studies have shown that during the process from the elastic stage, plastic stage to the failure stage in the stress-strain curve, there is always energy exchange with the outside world, and energy is constantly released to the outside world to maintain dynamic balance [39]. Through the experimental results of sandstone with different water content under cyclic loading, the water can weaken the sandstone underneath the Bohai Sea.…”
Section: Energy Evolution Characteristicsmentioning
confidence: 95%
“…In addition, the cyclic impact load generated by roadway mining will also accelerate the fragmentation of the base-angle area and other locations, increasing the difficulty of support in this area. Dai et al [10][11][12][13] studied the mechanical and energy dissipation characteristics of granite under a cyclic impact load, providing a theoretical basis for base-angle area support from the mechanical and energy perspectives. Moreover, Krykovskyi et al [14] carried out research on the strengthening effect of grouting the rock bolt onto weak surrounding rock, which enriched the strengthening theory of bolt support.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the high cost of in situ tests, many achievements have been made in the study of surrounding rock failure mode through laboratory tests. Dai et al [15] analyzed dynamic characteristics, damage characteristics, and energy dissipation and failure modes of rock with a single hole under cyclic impact load by using Split Hopkinson Pressure Bar (SHPB). Cheon et al [16] used CT technology to detect the failure of surrounding rock and distinguish damaged and failure areas.…”
Section: Introductionmentioning
confidence: 99%